Numerical Investigation of Aerodynamic Performance and Structural Analysis of a 3D J-Shaped Based Small-Scale Vertical Axis Wind Turbine - Oriol Bel Laveda; Marie-Alix Roche; Mohit Phadtare; Louise Sauge; Keerthana Jonnafer Xavier; Grishma Bhat; Divya Saxena; Jagmeet Singh Saini; Patrick G. Verdin (Energies, 2023)
Small vertical axis wind turbines (VAWTs) are often considered suitable for use in urban areas due to their compact design. However, they are also well known to offer poor performance at low wind speeds, which is a common situation in such environments. An optimised 3D J-shaped VAWT was designed from standard NACA 0015 blades and analysed numerically through computational fluid dynamics (CFD). A finite element analysis (FEA) was also carried out to ensure the model’s structural integrity. Optimal results were obtained with aluminium alloy hollow blades and stainless-steel struts with X-shaped beams, with internal ribs. Numerical results showed that the J-shaped VAWT achieved an 18.34% higher moment coefficient compared to a NACA 0015-based VAWT, indicating better self-starting abilities.